Modeling of Alanya District Demirtaş-Sedre Stream Flood Zone with MIKE Hydrological Model Program - Mehmet Dikici; Tasvire Gökce (Doğal Afetler ve Çevre Dergisi)
This study aims to evaluate the flood risks of Demirtaş-Sedre Stream in Alanya district of Antalya province by focusing on the effects of global climate change. The effects of global climate change on increased rainfall and natural disasters highlight the potential for human influence and resource use to pave the way for natural disasters, in particular. By using regional hydrological modeling methods, it is important in terms of determining flood risks in the Demirtaş-Sedre Stream basin and contributing to the development of strategies to reduce these risks. It provides important information about the mapping of the dangerous flood zones determined in the Demirtaş-Sedre Stream basin and the determination of the measures that can be taken in these areas. In this context, the role of natural and human factors on flood risks has been examined in detail and strategies for management have been proposed with the proposed methods. This study can be considered as an important step in terms of flood management planning and sustainability on a regional scale. In addition, the importance of such studies to understand the effects of global climate change at the local level and to build resilient communities against these effects is also emphasized. This article is an inspiring contribution to future studies on flood management and risk reduction strategies in both academic circles and local governments. 13. The data obtained from the Regional Directorate can be determined by calculating by statistical, synthetic or deterministic methods. Accordingly, dangerous flood zones have been identified. In this study, a study was carried out on modeling the Demirtaş-Sedre Stream in Alanya district of Antalya province with the MIKE hydrological model program, calculating the flood flow rate and estimating possible flood risks. Aerial photographs of the possible flood heights of the places where flood risk was determined and the current critical areas of flood spread areas were taken using UAV (Unmanned Aerial Vehicle) and analyzed in the conclusion part. According to the results of the analysis, it is important to predict and manage pre-flood disaster risks.